2017
DOI: 10.1103/physrevmaterials.1.053603
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of thermally activated edge dislocation unpinning from voids inα-Fe

Abstract: In this study, thermal unpinning of edge dislocations from voids in α-Fe is investigated by means of molecular dynamics simulations. The activation energy as a function of shear stress and temperature is systematically determined. Simulations with a constant applied stress are compared with dynamic simulations with a constant strain rate. We found that a constant applied stress results in a temperature dependent activation energy. The temperature dependence is attributed to the elastic softening of iron. If th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…One may even question the relevance of this concept in the case of any defect of finite size. In our model, we use alternatively the concept of obstacle shear resistance, that has been used to describe interactions with voids [39,40] and other precipitates [38]. It has been shown that implementing this resistance as a local rule in DD simulations is straightforward.…”
Section: Introducing Radiation Defectsmentioning
confidence: 99%
“…One may even question the relevance of this concept in the case of any defect of finite size. In our model, we use alternatively the concept of obstacle shear resistance, that has been used to describe interactions with voids [39,40] and other precipitates [38]. It has been shown that implementing this resistance as a local rule in DD simulations is straightforward.…”
Section: Introducing Radiation Defectsmentioning
confidence: 99%